Deformation And Stress Analysis Of 3D Printed Spanner Wrench - Ang, Cheau Hui (Universiti Sains Malaysia, 2022)
The 3D printing technology creates an object by printing the materials layer by layer, and thus the printing orientation used in creating the object highly influenced its mechanical properties. The goal of this study is to evaluate the mechanical behaviour of the 3D printing materials based on different printing orientations through mechanical testing such as tensile test, compression test, and bending test. The result shows that under different printing orientations, the 3D printing material, PLA behaves differently as the mechanical properties of PLA are dependent on the direction of force acting on it. The finite element simulation of each mechanical testing will be performed and the results obtained is compared with the results from the laboratory experiments. The project will then continue with the optimization in designing a 3D printed spanner wrench using different types of 3D printing materials, such as PLA and ABS. The 3D printed spanner wrench is optimized by changing the dimension of the spanner wrench, such as length and thickness. Then, the FEA simulation is done on the 3D printed spanner wrench at the condition of tightening or loosening the bolt using different values of forces. The result shows that the spanner with a longer length and a higher thickness makes the spanner becomes tougher and to withstand more force acting on it. By comparing the materials applied to it, PLA is more suitable to use in fabricating the spanner wrench than ABS due to its high tensile strength. For all the designed spanner wrench, the stress will concentrate at the sharp edge near the groove of the spanner wrench. The design of the spanner wrench needs to be further optimized.